The 1990's global grain situation and its impact on the food security of selected developing countries - Friedberg, Mark; Thomas, Marcelle (International Food Policy Research Institute, 1997)
Between 1993 and 1996, two developments occurred in world grain markets which posed a potential threat to the food security of import-dependent developing countries. First, starting in later 1994, real grain prices increased, limiting the ability of less developed countries (LDCs) to import grain during production shortfalls. Second, and perhaps more importantly, after 1993 the world stock-to-use ratios in the major food grains fell to record lows. This paper describes the nature of the 1990s grain price increase, and contrast it to the grain price crisis of the 1970s. The paper looks at 22 of the largest, poorest, and most import-dependent LDCs. The authors conclude that the grain price increase of the 1990s is relatively mild -- certainly relative to the grain price spike of the 1970s -- and does not appear to be indicative of a trend. The study offers some important lessons to be learned from the 1990s grain price increase.